Oral health problems and dental service utilization in children with hearing impairment: a narrative review - Parameswari, Amandita; Bahar, Armasastra; Adiatman, Melissa (International Journal Of Community Medicine And Public Health, 2023)
Children with hearing disability face challenges on accessing healthcare services caused by their lack of ability to express their oral health problems and affect their oral health status. This narrative review aims to explore oral health status in hearing impaired children and discuss in detail about dental service utilization in children with hearing impairment. Many studies assessed oral health status of children with hearing impairment. A comprehensive retrieval of the English literature from 2012 to 2022 was done in PubMed, ScienceDirect and ProQuest. Oral health assessments including dental caries, gingival problems and periodontal condition. Healthcare seeking behavior of the parents of hearing-impaired children is reflected by dental service utilization. Hearing impaired children have a high prevalence of caries, high caries activity and poor gingival condition compared to their counterparts. There are unmet dental treatment needs due to their dependence on parents or caregiver on decision making. Proper oral health educational method for hearing impaired children and their parents or caregiver is needed to improve oral health status and dental service utilization.